2016
DOI: 10.3748/wjg.v22.i29.6683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative staging for esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is known for its rapid progression and poor outcomes. China has the highest incidence and mortality in the world. Diagnoses made at early stages and accurate staging are associated with better outcomes, all of which can play a significant role in the selection of treatment protocols. ESCC is staged according to the widely accepted TNM system. Common imaging modalities used in staging ESCC before treatment include endoscopy, computed tomography (CT), positron emission t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…Riddell et al, conducted a study to assess the detection rate of esophageal cancer using high resolution T2-weighted MRI and found that MRI accurately detected only T3 and T4 cases [24]. Other studies showed that the combined T2-weighted and DWI scans detected 33% of T1, 58% of T2, 96% of T3 and 100% of T4 cases of esophageal cancer [25,26]. Cine MRI is a fast-imaging sequence of true steady-state precession that has been explored to dynamically display esophageal tumor and the risk of its invasion along with its motility [27].…”
Section: Discussionmentioning
confidence: 99%
“…Riddell et al, conducted a study to assess the detection rate of esophageal cancer using high resolution T2-weighted MRI and found that MRI accurately detected only T3 and T4 cases [24]. Other studies showed that the combined T2-weighted and DWI scans detected 33% of T1, 58% of T2, 96% of T3 and 100% of T4 cases of esophageal cancer [25,26]. Cine MRI is a fast-imaging sequence of true steady-state precession that has been explored to dynamically display esophageal tumor and the risk of its invasion along with its motility [27].…”
Section: Discussionmentioning
confidence: 99%
“…ESCC, a type of squamous epithelium differentiation of a malignant tumour within the oesophagus, accounts for the vast majority of oesophageal cancers [64, 65]. ESCC often presents in physiological or pathological stenosis of the oesophagus, and genetic factors, carcinogens, and/or chronic irritants may contribute to the pathogenesis of ESCC [64, 65]. The GSTP1 rs1695 A/G polymorphism is significantly related to the risk of ESCC in the Kashmiri population [42].…”
Section: Discussionmentioning
confidence: 99%
“…Core member of the NCECS Study Group: Xuan Liu,1 Qiaozhi Zhou,1 Yue Jiao,1 Ying Meng,1 Ye Zong,1 Qinggang Wang,1 Yinglin Niu,1 Hongmei Li,1 Li Yu,1 Haiying Zhao,1 Wenyan Li,1 Xun Yang,1 Li Zhang,1 Fandong Meng,1 Haiyi Hu,1 Yanhua Zhou,1 Shuxia Yu,2 Baohong Xu,3 Jianyu Hao,4 Aimin Wang,5 Zhen He,1 Chuntao Liu,1 Jian Wei,1 Yue Tian,1 Pei Zhang,1 Zhonglin Yu1…”
Section: Acknowledgmentsunclassified
“…1Department of Gastroenterology, Beijing Friendship Hospital, Capital Medical University, Beijing 100050, People’s Republic of China; 2Department of Gastroenterology, Daxing Hospital, Beijing 102600, People’s Republic of China; 3Department of Gastroenterology, Luhe Hospital, Beijing 101100, People’s Republic of China; 4Department of Gastroenterology, Beijing Chaoyang Hospital, Beijing 100020, People’s Republic of China; 5Department of Gastroenterology, The 252nd Hospital of PLA, Baoding 071000, People’s Republic of China.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation